Efficacy and safety of mirodenafil for patients with erectile dysfunction: a meta-analysis of three multicenter, randomized, double-blind, placebo-controlled clinical trials. (June 2014) - Du, Wan; Li, Jing; Fan, Ning; Shang, Panfeng; Wang, Zhiping; Ding, Hui
Abstract Aim: To systematically review evidence on the efficacy and safety of mirodenafil treatment in erectile dysfunction (ED) from randomised controlled trials. Methods: We searched PubMed, Embase and the Cochrane Library database up to March 2013. Two authors independently assessed study quality and extracted data. All data were analyzed using RevMan 5.0. Outcome measures assessed were the International Index of Erectile Function (IIEF), erectile function domain (EFD) score (primary), the Sexual Encounter Profile questions 2 and 3, and the response to the Global Assessment Questionnaire and adverse effects (secondary). Results: A total of 374 participants from three randomized controlled trials were identified in this meta-analysis. After 12 weeks treatment, mirodenafil was found to be more effective than placebo, and tolerability was good. The pooled results showed that the IIEF EFD score for 100 mg mirodenafil group was higher than placebo group (MD = 8.13, 95%CI: 6.64–9.61, p < 0.00001) and the mirodenafil group was also higher than placebo group in the changes from baseline for the IIEF EFD score (MD = 7.32, 95%CI: 5.56–9.07, p < 0.00001), respectively. The most common drug-related adverse events were flushing and headache (mirodenafil versus placebo: 15.8% versus 3.2%, 3.1% versus 0%; respectively). Conclusion: This meta-analysis suggested that mirodenafil is effective and well-tolerated therapy for ED.